Aboriginal music in contemporary: Echoes and exchanges - Hoefnagels, A. (Anna); Diamond, B. (Beverley) (2012)
First Nations, Inuit, and Métis music in Canada is dynamic and diverse, reflecting continuities with earlier traditions and innovative approaches to creating new musical sounds. Aboriginal Music in Contemporary Canada narrates a story of resistance and renewal, struggle and success, as indigenous musicians in Canada negotiate who they are and who they want to be. Comprised of essays, interviews, and personal reflections by Aboriginal and non-Aboriginal musicians and scholars alike, the collection highlights themes of innovation, teaching and transmission, and cultural interaction. Individual chapters discuss musical genres ranging from popular styles including country and pop to nation-specific and intertribal practices such as powwows, as well as hybrid performances that incorporate music with theatre and dance. As a whole, this collection demonstrates how music is a powerful tool for articulating the social challenges faced by Aboriginal communities and an effective way to affirm indigenous strength and pride. Juxtaposing scholarly study with artistic practice, Aboriginal Music in